MOMO syndrome associated with autism: a case report - Giunco, C. T. [UNESP] (2008)
This is a case report of macrosomia, obesity, macrocephaly and ocular abnormalities (MOMO syndrome) associated with autism. Studies on genetic or environmental syndromes associated with autism can provide genetic markers or uncover relevant events, and are very important for the definition of autism subgroups in future molecular research.